Strategy for the Treatment of Zygomatic-Coronoid Ankylosis - Santos, Anderson Maikon de Souza [UNESP]; Mendes, Bruno Coelho [UNESP]; Lima-Neto, Tiburtino José de [UNESP]; Paiva, Marcos Antônio Farias de; Villarim, Natália Lins de Souza; Santos, Murilo Quintão Dos; Faverani, Leonardo Perez [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Wolters Kluwer, 2020)
Zygomatic-coronoid ankylosis is a rare complication in maxillofacial trauma. Currently, less of 30 cases reported in the literature. The aim of this study was to report a case of zygomatic-coronoid ankylosis after trauma. A 26-year-old male, with zygomatic-coronoid ankylosis after 7 years of facial trauma, was treated by intraoral bilateral coronoidectomy. However, the literature continues to discuss the best approach, intraorally or extraorally. This study observed that the intraoral approach was easily performed and without complications.